Polyimide film with high glass transition temperature and preparation method thereof
By using polyamic acid, filler and lignin sulfonate in polymer films and casting and stretching treatment, the problem of insufficient heat resistance of polymer materials is solved, and a high glass transition temperature polyimide film is prepared, which is suitable for flexible optoelectronic devices processed at high temperatures.
Patent Information
- Application Number
- CN202510129255.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-05
- Publication Date
- 2025-04-25
AI Technical Summary
The heat resistance of traditional polymer materials is insufficient and cannot meet the processing needs of flexible optoelectronic devices in high temperature environments, which limits the development of related products.
Polyimide films with high glass transition temperatures are prepared by casting and bidirectional stretching by using polyamic acid as the main component and adding fillers such as alumina whiskers, talc and modified nanotubes, as well as lignin sulfonates.
The glass transition temperature of the polyimide film is increased, so that it can withstand higher processing temperatures, and is suitable for the production of miniaturized, lighter and foldable flexible optoelectronic devices.
Smart Images

Figure BDA0005261000380000061 
Figure BDA0005261000380000071 
Figure BDA0005261000380000091
Abstract
Description
Technical Field
[0001] The present application relates to the field of polymer technology, and more specifically, to a polyimide film with a high glass transition temperature and a preparation method thereof. Background Art
[0002] With the rapid development of the optoelectronics field, traditional inorganic materials represented by glass are increasingly unable to meet the product's demand for lightness and flexibility. Polymer materials have natural advantages in flexibility and transparency, and therefore show good application prospects in the field of optoelectronic devices. In recent years, with the development of concepts such as flexible wearable devices and flexible displays, the demand for polymer-based flexible substrate film materials for related products has also increased day by day.
[0003] However, the processing of flexible optoelectronic devices inevitably involves high temperature environments, such as the lead-free soldering process temperature of about 270°C, the flexible active matrix organic light-emitting diode panel preparation process temperature greater than 300°C, and the thin film transistor based on low-temperature polysilicon even requires a processing temperature of more than 400°C. The tolerance processing temperature of polymer materials (usually based on the glass transition temperature as a standard) often does not exceed 230°C, and cannot be used to manufacture flexible optoelectronic devices.
[0004] Regarding the above-mentioned related technologies, the inventors believe that currently, electronic products are gradually developing in the direction of miniaturization, lightness and foldability, which puts higher requirements on the heat resistance, dimensional stability and flexibility of flexible substrate materials. Traditional polymer materials are difficult to meet the heat resistance requirements, which will lead to restrictions on the development of related products. Summary of the invention
[0005] In the related art, it is difficult for traditional polymer materials to meet the requirements of heat resistance, which will limit the development of related products. In order to improve this defect, the present application provides a polyimide film with a high glass transition temperature and a preparation method thereof.
[0006] In a first aspect, the present application provides a polyimide film with a high glass transition temperature, using the following technical solution:
[0007] A polyimide film with a high glass transition temperature is prepared by casting and biaxially stretching a polyimide adhesive, wherein the polyimide adhesive comprises the following components in parts by weight: 43-45 parts of polyamic acid, 8-10 parts of filler, 2.5-3.5 parts of lignin sulfonate, and 400-420 parts of solvent; the filler comprises aluminum oxide whiskers, talcum powder, and modified nanotubes, wherein the modified nanotubes are allophane nanotubes with amino groups and phenyl groups on the surface, and the polyamic acid molecules have perfluoromethyl groups.
[0008] By adopting the above technical scheme, the present application uses polyamic acid as the main component, and adds filler and lignin sulfonate, and prepares a polyimide film by casting and stretching. The perfluoromethyl group in the polyamic acid can form a fluorine-hydrogen bond with extremely high bond energy in the system, which can effectively reduce the mobility of the polyimide segment itself. In the filler of the present application, the alumina whisker has a linear structure and has good rigidity. The aluminum hydroxyl group on the surface of the alumina whisker can form a hydrogen bond with the polyimide, thereby limiting the movement of the polyimide segment; talcum powder can induce the polyimide segment to be arranged regularly, so that the polyimide segment forms a filamentous structure, which is interwoven with the alumina whisker and the modified nanotubes to form a mesh structure, and the movement of the polyimide segment can be further limited by the synergistic effect with the hydrogen bond; the amino group and the phenyl group on the surface of the modified nanotube can make it have good dispersibility in the polyimide film, and the amino group can also form a hydrogen bond with the polyimide segment and other fillers. Lignin sulfonate can improve the dispersion effect of various fillers and increase the complexity of the hydrogen bond network. The aromatic rings in lignin sulfonate can also attract each other with the polyimide segments through the π-π stacking effect. In addition, the hydrogen bonding effect and the restriction of the network structure can effectively hinder the movement of the polyimide segments. In the polyimide film of the present application, the movement of the polyimide segments can be fully restricted and has a high glass transition temperature. Therefore, it is not easy to deform under heating conditions and can withstand high processing temperatures. It is particularly suitable for the production of miniaturized, lightweight, and foldable flexible optoelectronic devices.
[0009] Preferably, the polyamic acid is prepared according to the following method:
[0010] (1) adding a diamine monomer to a solvent, stirring and dissolving the monomer, to obtain a diamine solution for standby use; adding a dianhydride monomer to a solvent, stirring and dissolving the monomer, to obtain a dianhydride solution for standby use; the diamine monomer comprises 4,4-diaminodiphenyl ether, and the dianhydride monomer comprises biphenyltetracarboxylic anhydride and 4,4-hexafluoroisopropylidenephthalic anhydride;
[0011] (2) The diamine solution and the dianhydride solution are mixed and reacted in an ice water bath to obtain a polyamic acid.
[0012] By adopting the above technical solution, the present application uses fluorine-containing dianhydride monomers to participate in the reaction, introduces fluorine-containing groups, and obtains polyamic acid capable of forming fluorine-hydrogen bonds.
[0013] Preferably, the molar ratio of biphenyltetracarboxylic anhydride to 4,4-hexafluoroisopropylidenephthalic anhydride is 1:(2.4-2.8).
[0014] By adopting the above technical solution, the present application optimizes the ratio of dianhydride monomers, which helps to increase the glass transition temperature of the polyimide film.
[0015] Preferably, the diamine monomer further comprises 3,5-diaminobenzoic acid.
[0016] By adopting the above technical solution, 3,5-diaminobenzoic acid can introduce carboxyl groups into the polyimide film, which can improve the ability of the polyimide chain segments to form hydrogen bonds and help to increase the glass transition temperature of the polyimide film.
[0017] Preferably, the filler also includes at least one of nano titanium dioxide and glass powder.
[0018] By adopting the above technical scheme, nano titanium dioxide and glass powder can be used as fillers to improve the mechanical properties of polyimide film. Titanium dioxide and the carboxyl group introduced by 3,5-diaminobenzoic acid have a good cross-linking effect, which helps to limit the movement of polyimide chain segments and improve the glass transition temperature of the polyimide film.
[0019] Preferably, the modified nanotubes are prepared according to the following method:
[0020] (1) mixing allophane nanotubes and a silane coupling agent and adding them to an ethanol aqueous solution, firstly performing ultrasonic dispersion, then reacting them under a water bath heating condition, filtering them after the reaction, washing and drying the filter residue to obtain silanized nanotubes; the silane coupling agent comprises vinyl triethoxysilane;
[0021] (2) adding silanized nanotubes and monomers into water and mixing them, adding initiator KPS into the mixed solution, heating the mixture under nitrogen protection, and demulsifying, filtering and drying after the reaction to obtain modified nanotubes; in this step, the monomers include acrylamide and styrene.
[0022] By adopting the above technical scheme, the present application firstly uses vinyltriethoxysilane to treat the allophane nanotubes, introduces vinyl groups on the surface of the allophane nanotubes, and then introduces amino groups and phenyl groups through the copolymerization reaction of vinyl groups with monomers to obtain modified nanotubes.
[0023] Preferably, the molar ratio of acrylamide to styrene in the monomer is 1:(1.7-2.1).
[0024] By adopting the above technical solution, the present application optimizes the molar ratio of acrylamide and styrene, which helps to limit the movement of polyimide chain segments and improve the glass transition temperature of the polyimide film.
[0025] Preferably, the monomer further comprises dodecafluoroheptyl methacrylate.
[0026] By adopting the above technical solution, the fluorine-containing group introduced by dodecafluoroheptyl methacrylate can increase the number of fluorine-hydrogen bonds in the system, thereby further restricting the movement of the polyimide chain segments and increasing the glass transition temperature of the polyimide film.
[0027] Preferably, in the step (1) of preparing the modified nanotubes, the silane coupling agent used also includes tetraethyl orthosilicate.
[0028] By adopting the above technical scheme, the allophane nanotubes have good hydrophilicity, and the hydrolysis of tetraethyl orthosilicate can produce a hydrolysis product with four silanol groups, which is easy to combine with the allophane nanotubes, thereby increasing the number of silanol groups on the surface of the allophane nanotubes, which is beneficial to increase the total amount of vinyl groups on the surface of the silanized nanotubes and promote the full combination of the monomers on the surface of the nanotubes, thereby more effectively restricting the movement of the polyimide chain segments and increasing the glass transition temperature of the polyimide film.
[0029] In a second aspect, the present application provides a method for preparing a polyimide film with a high glass transition temperature, using the following technical solution.
[0030] A method for preparing a polyimide film with a high glass transition temperature comprises the following steps:
[0031] (1) mixing polyamic acid, filler, lignin sulfonate and solvent to obtain polyimide glue for standby use;
[0032] (2) The polyimide adhesive is subjected to casting processing and biaxial stretching to obtain a polyimide film with a high glass transition temperature.
[0033] By adopting the above technical scheme, in the method of the present application, a polyimide adhesive is first prepared, then the adhesive is solidified by a casting process, and a polyimide film with a high glass transition temperature is obtained after biaxial stretching.
[0034] In summary, this application has the following beneficial effects:
[0035] 1. In the polyimide film of the present application, the movement of the polyimide chain segments can be fully restricted and has a high glass transition temperature. Therefore, it is not easy to deform under heating conditions and can withstand high processing temperatures. It is particularly suitable for the production of miniaturized, lightweight, and foldable flexible optoelectronic devices.
[0036] 2. The present application uses fluorine-containing dianhydride monomers to participate in the reaction, introduces fluorine-containing groups, and obtains polyamic acid capable of forming fluorine-hydrogen bonds. Fluorine-hydrogen bonds can effectively reduce the mobility of the polyimide chain segments themselves, and help to increase the glass transition temperature of the polyimide film. DETAILED DESCRIPTION
[0037] The present application is further described in detail below in conjunction with embodiments, preparation examples and comparative examples. The raw materials involved in the present application can all be obtained commercially.
[0038] Preparation Example of Polyamic Acid
[0039] The following is an explanation using Preparation Example 1.
[0040] Preparation Example 1
[0041] In this preparation example, DMAc is selected as the solvent, 4,4-diaminodiphenyl ether is selected as the diamine monomer, and the dianhydride monomer is prepared by mixing biphenyltetracarboxylic anhydride and 4,4-hexafluoroisopropylidenephthalic anhydride in a molar ratio of 1:2.
[0042] In this preparation example, polyamic acid was prepared according to the following method:
[0043] (1) adding a diamine monomer to a solvent, stirring and dissolving the mixture at 20° C. to obtain a diamine solution for later use; adding a dianhydride monomer to a solvent, stirring and dissolving the mixture at 20° C. to obtain a dianhydride solution for later use;
[0044] (2) The diamine solution and the dianhydride solution were mixed in a molar ratio of dianhydride monomer:diamine monomer=1:1, and reacted in an ice water bath at 0°C for 5 hours to obtain polyamic acid.
[0045] As shown in Table 1, the difference between Preparation Examples 1-4 is that the molar ratio of biphenyltetracarboxylic anhydride to 4,4-hexafluoroisopropylidenephthalic anhydride (hereinafter referred to as dianhydride ratio) is different.
[0046] Table 1 Dianhydride ratio
[0047]
[0048]
[0049] Preparation Example 5
[0050] The difference between this preparation example and preparation example 4 is that the diamine monomer further includes 3,5-diaminobenzoic acid, and the molar ratio of 3,5-diaminobenzoic acid to 4,4-diaminodiphenyl ether is 1:1.
[0051] Preparation example of modified nanotubes
[0052] The following is an explanation using Preparation Example 6.
[0053] Preparation Example 6
[0054] In this preparation example, the average inner diameter of the allophane nanotubes is 1 nm, the average outer diameter is 2.8 nm, and the average tube length is 450 nm. The silane coupling agent used in this preparation example is vinyl triethoxysilane, and the weight ratio of vinyl triethoxysilane to the allophane nanotubes is 1:10. The monomers selected in this preparation example are acrylamide and styrene, and the molar ratio of acrylamide to styrene is 1:1.4.
[0055] In this preparation example, the modified nanotubes were prepared according to the following method:
[0056] (1) mixing allophane nanotubes and a silane coupling agent and adding them to an ethanol aqueous solution to obtain a mixed solution with an allophane nanotube content of 15 wt%, firstly subjecting the mixed solution to ultrasonic dispersion at a power of 500 W for 1 h, then subjecting the mixed solution to a reaction in a water bath at 95° C. for 3 h, filtering after the reaction, washing and drying the filter residue to obtain silanized nanotubes;
[0057] (2) Silylated nanotubes, monomers and water are mixed in a weight ratio of 100:25:2000, and an initiator KPS is added to the mixed solution in an amount equivalent to 1 wt% of the monomers. The mixed solution is heated at 80° C. for 6 h under nitrogen protection. After the reaction is completed, the emulsion is first broken and then filtered, and the filter cake is dried to obtain modified nanotubes.
[0058] As shown in Table 2, the difference between Preparation Examples 6-9 is that the molar ratio of acrylamide to styrene is different.
[0059] Table 2 Molar ratio of acrylamide and styrene
[0060] sample Acrylamide:Styrene Preparation Example 6 1:1.4 Preparation Example 7 1:1.7 Preparation Example 8 1:1.9 Preparation Example 9 1:2.1
[0061] Preparation Example 10
[0062] The difference between this preparation example and preparation example 9 is that the monomer used in step (2) of preparing the modified nanotubes also includes dodecafluoroheptyl methacrylate, and the molar ratio of acrylamide to dodecafluoroheptyl methacrylate is 1:0.3.
[0063] Preparation Example 11
[0064] The difference between this preparation example and preparation example 10 is that in step (1) of preparing the modified nanotubes, the silane coupling agent used also includes tetraethyl orthosilicate, and the weight ratio of tetraethyl orthosilicate to allophane nanotubes is 1:20.
[0065] Example
[0066] Examples 1-5
[0067] The following description is given by taking Example 1 as an example.
[0068] Example 1
[0069] In this embodiment, the solvent is DMAc, the polyamic acid is prepared according to the method of Preparation Example 1, the filler includes aluminum oxide whiskers, talcum powder and modified nanotubes, and the weight ratio of aluminum oxide whiskers, talcum powder and modified nanotubes is 1:0.5:2.3; the average diameter of the aluminum oxide whiskers is 60nm, and the average length is 5.5μm; the specification of talcum powder is 5000 mesh, the modified nanotubes are prepared according to the method of Preparation Example 6, and the lignin sulfonate is sodium lignin sulfonate.
[0070] This embodiment provides a polyimide film with a high glass transition temperature. The polyimide film is made by casting and biaxially stretching a polyimide adhesive. The polyimide adhesive includes the following components: 43 kg of polyamic acid, 8 kg of filler, 2.5 kg of lignin sulfonate, and 400 kg of solvent.
[0071] This embodiment provides a method for preparing a polyimide film with a high glass transition temperature, comprising the following steps:
[0072] (1) mixing polyamic acid, filler, lignin sulfonate and solvent to obtain polyimide glue for standby use;
[0073] (2) The polyimide adhesive solution is subjected to a casting process. Specifically, the polyimide adhesive solution is coated on a glass plate by a casting method, placed in an oven for temperature rise and curing, and then biaxially stretched to obtain a polyimide film with a high glass transition temperature. The thickness of the film is 70 μm.
[0074] In the above-mentioned casting operation, the temperature rising program in the oven is: heat to 150 ℃ in 1 hour, keep warm for 1 hour, heat to 175 ℃ in 0.5 hour, keep warm for 1 hour, heat to 200 ℃ in 0.5 hour, keep warm for 1 hour, heat to 250 ℃ in 0.5 hour, keep warm for 1 hour, heat to 300 ℃ in 0.5 hour, keep warm for 1 hour, and then wait for natural cooling to 25 ℃.
[0075] As shown in Table 3, the difference between Examples 1-5 mainly lies in the different raw material ratios of the polyimide glue.
[0076] Table 3 Raw material ratio of polyimide glue
[0077]
[0078] Embodiment 5-9
[0079] As shown in Table 4, the difference between Examples 5-9 is that the preparation examples of polyamic acid are different.
[0080] Table 4 Preparation example of polyamic acid
[0081] sample Preparation Example Example 5 Preparation Example 1 Example 6 Preparation Example 2 Example 7 Preparation Example 3 Example 8 Preparation Example 4 Example 9 Preparation Example 5
[0082] Example 10
[0083] The difference between this embodiment and embodiment 9 is that the filler further includes glass powder, the average particle size of the glass powder is 2 μm, and the weight ratio of the aluminum oxide whisker to the glass powder is 1:0.15.
[0084] Embodiment 11
[0085] The difference between this embodiment and embodiment 10 is that the filler further includes nano titanium dioxide, the average particle size of the nano titanium dioxide is 65 nm, and the weight ratio of the aluminum oxide whisker to the nano titanium dioxide is 1:0.1.
[0086] Examples 11-16
[0087] As shown in Table 5, the difference between Examples 11-16 is that the preparation examples of the modified nanotubes are different.
[0088] Table 5 Preparation example of modified nanotubes
[0089] sample Preparation Example Embodiment 11 Preparation Example 6 Example 12 Preparation Example 7 Example 13 Preparation Example 8 Embodiment 14 Preparation Example 9 Embodiment 15 Preparation Example 10 Example 16 Preparation Example 11
[0090] Comparative Example
[0091] Comparative Example 1
[0092] The difference between this comparative example and Example 1 is that the components of the polyimide adhesive do not include fillers.
[0093] Comparative Example 2
[0094] The difference between this comparative example and Example 1 is that the filler component does not include aluminum oxide whiskers.
[0095] Comparative Example 3
[0096] This comparative example is different from Example 1 in that the filler component does not include talc.
[0097] Comparative Example 4
[0098] The difference between this comparative example and Example 1 is that the filler component does not include modified nanotubes.
[0099] Comparative Example 5
[0100] The difference between this comparative example and Example 1 is that the components of the polyimide glue do not include lignin sulfonate.
[0101] Comparative Example 6
[0102] The difference between this comparative example and Example 1 is that the dianhydride monomer for preparing the polyamic acid does not include 4,4-hexafluoroisopropylidenephthalic anhydride.
[0103] Performance testing methods
[0104] DMA test was used to characterize the glass transition temperature of the polyimide film. The specific operation method was as follows: the polyimide film was cut into rectangular strips of 40 mm × 60 mm, and a dynamic stretching mode was used under N2 atmosphere. The heating rate was 5°C / min, the heating range was 25-500°C, and the test frequency was 1 Hz. The results are shown in Table 6.
[0105] Table 6 Glass transition temperature test results
[0106]
[0107] Combining Examples 1-5 and Comparative Examples 1-6 and Table 6, it can be seen that the glass transition temperatures measured in Examples 1-5 are all higher than those in Comparative Examples 1-6. This is because the perfluoromethyl group reduces the mobility of the polyimide segments themselves, the filler forms hydrogen bonds with the polyimide while providing rigidity, the lignin sulfonate increases the complexity of the hydrogen bond network, and attracts the polyimide segments through the π-π stacking effect, and the talc in the filler induces the polyimide segments to form a filamentous structure, which is interwoven with the alumina whiskers and the modified nanotubes to form a mesh structure. Through the synergistic effect of hydrogen bonding, the mesh structure, and the physical properties of the filler itself, the movement of the polyimide segments can be fully restricted, and has a higher glass transition temperature.
[0108] Combining Example 1 and Comparative Example 1 and Table 6, it can be seen that the glass transition temperature measured in Example 1 is higher than that in Comparative Example 1. The main reason is that Comparative Example 1 lacks filler, which affects the formation of the network structure and hydrogen bonds, and thus cannot fully restrict the movement of the polyimide chain segments.
[0109] Combining Example 1 and Comparative Example 2 and Table 6, it can be seen that the glass transition temperature measured in Example 1 is higher than that in Comparative Example 2. The main reason is that Comparative Example 2 lacks aluminum oxide whiskers, which affects the formation of the network structure.
[0110] Combining Example 1 and Comparative Example 3 and Table 6, it can be seen that the glass transition temperature measured in Example 1 is higher than that in Comparative Example 3. The main reason is that Comparative Example 3 lacks talc powder, which cannot fully induce the polyimide segment to form a filamentous structure, affecting the formation of a network structure, and thus cannot fully restrict the movement of the polyimide segment.
[0111] Combining Example 1 and Comparative Example 4 and Table 6, it can be seen that the glass transition temperature measured in Example 1 is higher than that in Comparative Example 4. The main reason is that Comparative Example 4 lacks modified nanotubes, which affects the network structure and the formation of hydrogen bonds, and thus cannot fully restrict the movement of the polyimide chain segments.
[0112] Combining Example 1 and Comparative Example 5 and Table 6, it can be seen that the glass transition temperature measured in Example 1 is higher than that in Comparative Example 5. The main reason is that Comparative Example 5 lacks lignin sulfonate, which affects the complexity of hydrogen bonds, and the remaining components cannot effectively attract the polyimide chain segments through the π-π stacking effect, thereby failing to fully restrict the movement of the polyimide chain segments.
[0113] Combining Example 1 and Comparative Example 6 and Table 6, it can be seen that the glass transition temperature measured in Example 1 is higher than that in Comparative Example 6. The main reason is that the polyamic acid in the comparative example lacks fluorine-containing groups and cannot fully restrict the mobility of the polyimide chain segments through fluorine-hydrogen bonds.
[0114] It can be seen from Examples 5-8 and Table 6 that when the molar ratio of biphenyltetracarboxylic anhydride to 4,4-hexafluoroisopropylidenephthalic anhydride is 1:(2.4-2.8), it helps to increase the glass transition temperature of the polyimide film.
[0115] It can be seen from Example 8 and Example 9 and Table 6 that 3,5-diaminobenzoic acid can introduce carboxyl groups into the polyimide film, improve the ability of the polyimide chain segments to form hydrogen bonds, and help to increase the glass transition temperature of the polyimide film.
[0116] It can be seen from Example 9, Examples 10-11 and Table 6 that the addition of glass powder and nano-titanium dioxide helps to restrict the movement of polyimide chain segments, effectively increasing the glass transition temperature of the polyimide film.
[0117] It can be seen from Example 11, Examples 12-14 and Table 6 that when the molar ratio of acrylamide to styrene in the monomer is 1:(1.7-2.1), it helps to restrict the movement of the polyimide chain segments and improve the glass transition temperature of the polyimide film.
[0118] Combining Example 14, Example 15 and Table 6, it can be seen that the glass transition temperature measured in Example 15 is higher. This is because the fluorine-containing group introduced by dodecafluoroheptyl methacrylate can increase the number of fluorine-hydrogen bonds in the system, thereby further restricting the movement of the polyimide chain segments and increasing the glass transition temperature of the polyimide film.
[0119] Combining Example 15, Example 16 and Table 6, it can be seen that the glass transition temperature measured in Example 16 is relatively high. This is because the allophane nanotubes have good hydrophilicity, and the hydrolysis of tetraethyl orthosilicate can produce a hydrolysis product with four silanol groups. The hydrolysis product is easily combined with the allophane nanotubes, thereby increasing the number of silanol groups on the surface of the allophane nanotubes, which is beneficial to increase the total amount of vinyl groups on the surface of the silanized nanotubes, promote the full combination of the monomer on the surface of the nanotubes, thereby more effectively restricting the movement of the polyimide chain segments and improving the glass transition temperature of the polyimide film.
[0120] The above embodiments are merely explanations of the present application and are not limitations of the present application. After reading this specification, those skilled in the art may make modifications to the embodiments of the present application without any creative contribution as needed. However, as long as they are within the scope of the claims of the present application, they are protected by the patent law.
Claims
1. A polyimide film with a high glass transition temperature, characterized in that: The polyimide film is made of polyimide glue after casting and biaxial stretching. The polyimide glue comprises the following components in parts by weight: 43-45 parts of polyamic acid, 8-10 parts of filler, 2.5-3.5 parts of lignin sulfonate, and 400-420 parts of solvent; the filler comprises aluminum oxide whiskers, talcum powder and modified nanotubes, the modified nanotubes are allophane nanotubes with amino groups and phenyl groups on the surface, and the polyamic acid molecules have perfluoromethyl groups.
2. The polyimide film with a high glass transition temperature according to claim 1, characterized in that: The polyamic acid is prepared according to the following method: (1) adding a diamine monomer to a solvent, stirring and dissolving the monomer, to obtain a diamine solution for standby use; adding a dianhydride monomer to a solvent, stirring and dissolving the monomer, to obtain a dianhydride solution for standby use; the diamine monomer comprises 4,4-diaminodiphenyl ether, and the dianhydride monomer comprises biphenyltetracarboxylic anhydride and 4,4-hexafluoroisopropylidenephthalic anhydride; (2) The diamine solution and the dianhydride solution are mixed and reacted in an ice water bath to obtain a polyamic acid.
3. The polyimide film with a high glass transition temperature according to claim 2, characterized in that: The molar ratio of the biphenyltetracarboxylic anhydride to 4,4-hexafluoroisopropylidenephthalic anhydride is 1:(2.4-2.8).
4. The polyimide film with a high glass transition temperature according to claim 2, characterized in that: The diamine monomer also includes 3,5-diaminobenzoic acid.
5. The polyimide film with a high glass transition temperature according to claim 4, characterized in that: The filler also includes at least one of nano titanium dioxide and glass powder.
6. The polyimide film with a high glass transition temperature according to claim 1, characterized in that: The modified nanotubes are prepared according to the following method: (1) mixing allophane nanotubes and a silane coupling agent and adding them to an ethanol aqueous solution, firstly performing ultrasonic dispersion, then reacting them under a water bath heating condition, filtering them after the reaction, washing and drying the filter residue to obtain silanized nanotubes; the silane coupling agent comprises vinyl triethoxysilane; (2) adding silanized nanotubes and monomers into water and mixing them, adding initiator KPS into the mixed solution, heating the mixture under nitrogen protection, and demulsifying, filtering and drying after the reaction to obtain modified nanotubes; in this step, the monomers include acrylamide and styrene.
7. The polyimide film with a high glass transition temperature according to claim 6, characterized in that: The molar ratio of acrylamide to styrene in the monomer is 1:(1.7-2.1).
8. The polyimide film with a high glass transition temperature according to claim 7, characterized in that: The monomers also include dodecafluoroheptyl methacrylate.
9. The polyimide film with a high glass transition temperature according to claim 6, characterized in that: In the step (1) of preparing the modified nanotubes, the silane coupling agent used also includes tetraethyl orthosilicate.
10. The method for preparing a polyimide film with a high glass transition temperature according to any one of claims 1 to 9, characterized in that: The following steps are involved: (1) mixing polyamic acid, filler, lignin sulfonate and solvent to obtain polyimide glue for standby use; (2) The polyimide adhesive is subjected to casting processing and biaxial stretching to obtain a polyimide film with a high glass transition temperature.
Citation Information
Patent Citations
Soluble and high-temperature resistant aromatic polyimide and preparation method thereof
CN101787129A
Polyimide film as well as preparation method and application thereof
CN118206783A
Cited By
Preparation method of insulating high-temperature-resistant polyimide-ceramic composite material
CN121249150A
Preparation method of insulating high-temperature-resistant polyimide-ceramic composite material
CN121249150B